Gravity Data Decomposition Based on Spectral Analysis and Halo Wavelet Transform, Case Study at Birdâs Head Peninsula, West Papua - Handyarso, Accep; Kadir, Wawan Gunawan A. (Journal of Engineering and Technological Sciences, 2017)
Gravity imagery is commonly used in the preliminary study of sedimentary basins. Gravity data have an excellent lateral resolution but poor vertical resolution. The gravity response represents the superposition of all elements of differing density contrasts and depthsfor a given region below the surface. The ability to perform depth-based gravity data decomposition is important for the interpretation of the data. This can be achieved by combiningspectral analysis withthe Halo wavelet transform. The decomposition method was tested using synthetic data as well as field data collected at Birdâs Head Peninsula, West Papua. Examination of the proposed method using the synthetic data produced satisfactory results that corresponded well to the models. The test using the field data clearly imaged anticline structures that formed due tothe ongoing collision of the Australia Continental Plate and the Pacific Oceanic Plate. In part of the Lengguru Fold and Thrust Belt, the folding structures are not imaged at depths greater than ~6 km. We proposethat folding structures are not found at deeper levels. The gravity imagery also indicates that the Sorong Fault Zonebreaks apart into several segments, which causes other perpendicular lineaments(strike-slip faulting). These strike-slip faults are clearly visible in the Birdâs Head Region.